2016
DOI: 10.1093/occmed/kqw089
|View full text |Cite
|
Sign up to set email alerts
|

Core competencies for UK occupational health nurses: a Delphi study

Abstract: BackgroundOccupational health nurses (OHNs) play a pivotal role in the delivery of occupational health (OH) services. Specific competency guidance has been developed in a number of countries, including the UK. While it is acknowledged that UK OHN practice has evolved in recent years, there has been no formal research to capture these developments to ensure that training and curricula remain up-to-date and reflect current practice.AimsTo identify current priorities among UK OHNs of the competencies required for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(17 citation statements)
references
References 17 publications
0
10
0
4
Order By: Relevance
“…Supervision within the team contributes to safer and less stressed nurses especially when ethical dilemmas are discussed, and professional development influences high-quality nursing. However, Lallo, et al [9] argue that a high quality of care follows general principles of assessment (standardized) more than research methods (theory in nursing education); for expert nurse. Moreover, mental support, especially during newly graduated nurses' first-year experiences, decreases their anxiety regarding being insufficient and alone at work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supervision within the team contributes to safer and less stressed nurses especially when ethical dilemmas are discussed, and professional development influences high-quality nursing. However, Lallo, et al [9] argue that a high quality of care follows general principles of assessment (standardized) more than research methods (theory in nursing education); for expert nurse. Moreover, mental support, especially during newly graduated nurses' first-year experiences, decreases their anxiety regarding being insufficient and alone at work.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to facilitate future nurse's assignments in health care, educators in universities and clinical settings need innovative pathways that bring students and clinicians together as team members to overcome the gap between theory and practice [4]. Nurse's had several task, one is preventative care [7,8]; however, when more care is needed, nursing must be performed in collaboration according to the team's practical, empirical and personal knowledge [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…Mixed methods were used in identifying the competencies for hosptial managers and community health service managers [6] , [12] . Other studies applied merely qualitative methods to identify the required leadership and managerial competencies for hospital managers [14] [16] . These studies are limited in that the identified competencies were not confirmed by its validity and reliability through statistical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…En nuestros resultados encontramos que la mayoría del personal no falta al trabajo, sin embargo el 37.5 % de los pacientes con SFC faltan a trabajar, siendo este resultado consistente con lo reportado por Huibers. 8 Al igual que en lo mencionado por Garcia et al 9 , Boschman et al 10 y Lallo et al 11 , quienes realizaron estudios en personal de enfermería. Encontraron que la mayor parte del personal se encontró en la cuarta década de la vida y predominando el sexo femenino.…”
Section: Discussionunclassified